2012
DOI: 10.1016/j.jacc.2011.11.059
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Fluorine-18 Positron Emission Tomography/Computed Tomography for Identification of Cardiovascular Implantable Electronic Device Infections

Abstract: PET/CT is useful in differentiating between CIED infection and recent post-implant changes. It may guide appropriate therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
155
1
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(174 citation statements)
references
References 15 publications
5
155
1
13
Order By: Relevance
“…15 Supplementary diagnostics should include transoesophageal echocardiography to visualise leads, valvular involvement and vegetation, 15 and in some cases 18-fluorodeoxyglucose positron emission tomography (FDG-PET). 34,35 …”
mentioning
confidence: 99%
“…15 Supplementary diagnostics should include transoesophageal echocardiography to visualise leads, valvular involvement and vegetation, 15 and in some cases 18-fluorodeoxyglucose positron emission tomography (FDG-PET). 34,35 …”
mentioning
confidence: 99%
“…15,18,22,[26][27][28][29][30][31] However, one caveat is that the majority of studies evaluating diagnostic accuracy in suspected CIED-GPI only include confirmed cases or those with medium-to-high pre-test probability. Paradoxically, patients at the opposite end of the spectrum (with a lower pre-test probability of infection at initial presentation) are generally considered to pose a greater diagnostic challenge and by comparison are relatively underrepresented in these studies; arguably, a novel non-invasive diagnostic tool would be most useful in this group of patients, and further studies assessing the performance of 18 F-FDG in this group are desirable.…”
Section: Historical Perspectivementioning
confidence: 99%
“…26 Protez kapak veya İK cihaz enfeksiyonu tanı-sında 18 F-floro-deoksiglikoz (FDG)-PET/BT kullanılarak pek çok çalışma yapılmıştır. 23,24,[27][28][29] Protez kapaklı 72 hastalık bir çalışmada, Duke kriterlerine, anormal FDG tutulumun eklenmesiyle duyarlılık %70'den %97'ye çıkmıştır. Daha önemlisi, Duke kriterlerine göre, muhtemel PKE tanısı alan hastaların %43'ünde endokardit tanısı kesinleştirilmiş veya dışlanmıştır.…”
Section: Manyeti̇k Rezonans Görüntülemeunclassified
“…Ayrıca, yüzeyel enfeksiyon, derin cep enfeksiyonundan ayırt edilebilmiştir. 29 Yüzeyel enfeksiyon antibiyotikle tedavi edilirken, derin cep infeksiyonunda tüm sistem çıkarılmaktadır.…”
Section: Manyeti̇k Rezonans Görüntülemeunclassified
See 1 more Smart Citation